Design and Development of a Low-Cost Quadruped Robot for Educational Robotics Applications - Trupti D. Bahirat; Kshitija R. Bhadake; Vishal P. Bargal; Vaibhav E. Bendre; Naveen Kumar (International Journal of Manufacturing and Production Engineering, 2026)
The locomotion of the quadruped robots resembles that of four-legged animals and can be used on surfaces that wheeled robots cannot navigate. The paper is a design and development report on a low-cost quadruped robot that has been designed to be used in educational and experimental robotics. The robot is a lightweight and modular robotic system consisting of a combination of mechanical design, embedded control, and wireless communication. The actuation of the joint is carried out by the use of servo motors, and the control of motion is carried out by an Arduino Nano microcontroller. The mechanical design is made with lightweight 3D-printed parts such as coxa, femur and tibia links. To provide smartphone control and a Bluetooth interface, a Bluetooth module is used, and the voltage is steadied by a buck converter to supply the electronic parts. To provide a stable locomotion and balance a crawl gait algorithm is used. Through experimental testing, it has been proved that the robot is capable of walking and turning on flat surfaces with a reasonable degree of stability. It has been shown through the developed system that a useful quadruped robot could be built with relatively low cost and readily available parts and, therefore, could be used in robotics education as well as introductory research.
Keywords: Arduino NANO; educational robotics; gait algorithm; quadruped robot; robotic locomotion; servo motors